2016
DOI: 10.1248/bpb.b16-00258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Skin Permeability and Toxicological Properties of Amorphous Silica Particles

Abstract: Nanomaterials (NMs) are defined as those which have nanostructured components less than 100 nm in diameter. They are widely used in various fields such as medicine, cosmetics, and the food industry. However, the toxicological effects of NMs are less well understood than their applications. In particular, the skin is exposed to the environment at all times, so is easily influenced by NMs. In this study, we investigated the skin permeability and toxicological properties of well-dispersed amorphous silica particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…More recently, Matsuo et al . exposed mice to high doses (125 μg/ear/day) for 28 days and observed skin penetration of 70 nm SiNPs, but detected minimal dermal toxicity 24 . Due to the increased dermal exposure of SiNPs and the prevalence of inflammatory skin conditions 2527 , more dermal toxicity studies are warranted to examine the effects of physiologically relevant doses of NPs on both healthy and diseased skin models.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Matsuo et al . exposed mice to high doses (125 μg/ear/day) for 28 days and observed skin penetration of 70 nm SiNPs, but detected minimal dermal toxicity 24 . Due to the increased dermal exposure of SiNPs and the prevalence of inflammatory skin conditions 2527 , more dermal toxicity studies are warranted to examine the effects of physiologically relevant doses of NPs on both healthy and diseased skin models.…”
Section: Introductionmentioning
confidence: 99%
“…Iron-based nanoparticles (FeNP), gold nanoparticles (AuNP), palladium nanoparticles (PdNP), nickel nanoparticles (NiNP), AgNP, SiNP, and metal-based quantum dots (QD) have all been associated with penetration of the skin (Baroli et al 2007; Chu et al 2007; Filon et al 2011, 2016; Labouta et al 2011; Hirai et al 2012a; Rancan et al 2012; George et al 2014; Crosera et al 2016; Kraeling et al 2018). Moreover, many of these studies have established a relationship between decreased particle size and increased potential for skin permeation (Ryman-Rasmussen et al 2006; Sonavane et al 2008; Matsuo et al 2016; Raju et al 2018). Hydrophobicity, surface charge, and morphology are additional properties that have been shown to be influential in the capacity for these nanomaterials to pass through the stratum corneum (Rancan et al 2012; Lee et al 2013; Iannuccelli et al 2014; Fernandes et al 2015; Tak et al 2015; Mahmoud et al 2018).…”
Section: Metal Nanomaterials and Dermal Hypersensitivitymentioning
confidence: 99%
“…16 Skin permeability and toxicological property of well-dispersed amorphous silica particles for sizes ranging from 70 nm to 1000 nm was investigated using an in vitro artificial skin model for the penetration assay and in vivo mice model for penetration and toxicity evaluation. 17 The result suggested that decreasing particle size (down to 70 nm) increases NPs skin permeability. Most current studies on the distribution and toxicology of NPs on systems or organs emphasize the liver, kidney, lungs, and gastrointestinal (GI) tract, and skin penetration studies are largely qualitative and sometimes contradictory.…”
Section: Introductionmentioning
confidence: 99%